The Role of R&D and Technology Diffusion in Climate Change Mitigation New Perspectives Using the WITCH Model - Bosetti, Valentina (OECD Publishing, 2009)
This paper uses the WITCH model, a computable general equilibrium model with endogenous technological change, to explore the impact of various climate policies on energy technology choices and the costs of stabilising greenhouse gas concentrations. Current and future expected carbon prices appear to have powerful effects on R&D spending and clean technology diffusion. Their impact on stabilisation costs depends on the nature of R&D: R&D targeted at incremental energy efficiency improvements has only limited effects, but R&D focused on the emergence of major new low-carbon technologies could lower costs drastically if successful - especially in the non-electricity sector, where such low-carbon options are scarce today. With emissions coming from multiple sources, keeping a wide range of options available matters more for stabilisation costs than improving specific technologies. Due to international knowledge spillovers, stabilisation costs could be further reduced through a complementary, global R&D policy. However, a strong price signal is always required
Keywords: Economics